The Relationship between the Use of Health Information Systems and Community Satisfaction with Health Services in Primary Health Care: a Systematic Review - Nathan, Daniel Setiawan; Rostiaty, Erti (International Medical Journal Corp. Ltd, 2024)
Background: The goal of this study is to showed the relationship between the use of health information systems and community satisfaction with health services in primary health care. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. Several different online reference sources, like Pubmed and SagePub, were used to do this. Result: In the PubMed database, the results of our search brought up561 articles, whereas the results of our search on SagePub brought up 447 articles. The results of the search conducted for the last year of 2013 yielded a total 139 articles for PubMed and 67 articles for SagePub. In the end, we compiled a total of 12 papers, 8 of which came from PubMed and 4 of which came from SagePub. We included three research that met the criteria. Conclusion: Implementing a health information system in PHC is beneficial for patients, according to research. This naturally adds value to the service, which contributes to the high level of customer satisfaction.